The effects of plyometric warm-up on lower limb muscle activity and time to 10m in the backstroke swimming start - Barkwell, G. E.; Dickey, J. P. (International Journal of Human Movement and Sports Sciences, 2018)
The backstroke swim start is an explosive, discrete skill. Swimmers often perform plyometric warm-up protocols, such as repeated jumps, prior to their race. The purpose of this study was to determine the impact of repeated drop jumps performed immediately prior to a backstroke start. Nine elite backstroke swimmers performed three starts after a standard swimming warm-up, and three after an additional plyometric warm-up (three drop jumps from a height of 0.4 m) prior to each start. Timing and peak activation of gluteus maximus and vastus lateralis activity were measured using wireless surface electromyography. Hip and knee angles, wall contact time, head entry distance and time to 10 m were recorded using digital video cameras positioned at the side of the pool. On average, starts performed after the plyometric warm-up had a 0.10.09 s longer time to 10 m, peak gluteus maximus activity occurred 0.090.13 s later and peak vastus lateralis activity occurred 0.150.16 s earlier. Head entry distance was inversely proportional to time to 10 m (r = -0.80) across both conditions and should be considered as a training target. Performing plyometric warm-ups immediately prior to races may have a negative impact on backstroke start time to 10 m.